Nutritional Interventions During Pregnancy and Their Impact on Neonatal Stunting: A Systematic Review of Evidence from Low and Middle-Income Countries - Pinda Hutajulu; Wilhelma N. Ditaelis (Lembaga Pengembangan Kinerja Dosen, 2025)
Stunting continues to pose a serious public health issue in low- and middle-income countries (LMICs), affecting over 148 million children under five globally in 2022. Maternal nutrition during pregnancy plays a crucial role in determining birth outcomes and reducing the risk of stunting. This systematic review assessed the impact of nutritional interventions during pregnancy on stunting prevention and neonatal health in LMICs. A comprehensive search of PubMed, Scopus, Cochrane Library, and Google Scholar was conducted for studies published from 2005 to 2025, including RCTs, quasi-experimental studies, systematic reviews, meta-analyses, and analytical observational studies involving pregnant women in LMIC settings. From 6,204 initial records, 20 studies with over 114,000 participants were included. The review found that energy-protein supplementation reduced stunting risk by up to 28%, while multiple micronutrient supplements lowered the incidence of low birth weight and small-for-gestational-age (SGA) infants. Vitamin D supplementation also significantly reduced SGA risk. Nutrition education and counseling improved maternal dietary practices and lowered stunting rates. Conversely, maternal undernutrition—indicated by low BMI—was associated with a 22% increased risk of child stunting. These findings highlight the effectiveness of both nutrition-specific and nutrition-sensitive interventions during pregnancy. Integrated approaches combining supplementation and education should be prioritized in public health strategies.